First and second order necessary conditions of optimality for impulsive control problems - Aram Arutyunov (2003)
We present first and second order necessary conditions of optimality for a general class of nonlinear measure driven dynamic control systems subject to both equality and inequality endpoint state constraints. An important feature of our result is that the conditions remain informative even for abnormal control processes. Our result is obtained by decoding the necessary conditions of optimality for an abstract minimization problem with equality and inequality type constraints and constraints given by convex cone.